CLINICAL SPECTRUM OF SNAKE BITE AND THERAPEUTIC CHALLENGES: Clinical Spectrum of Snake Bite - Maken, Ghulam Rasool; Sheikh, Muhammad Zubair; Satti, Shahzeb Ahmed (Pakistan Armed Forces Medical Journal, 2008)
.